2020
DOI: 10.1021/acsaem.0c01300
|View full text |Cite
|
Sign up to set email alerts
|

Collisional Electron Transfer Route between Homogeneous Porphyrin Dye and Catalytic TiO2/Re(I) Particles for CO2 Reduction

Abstract: Dye detachment issue in the TiO 2 -mediated dye-sensitized photocatalytic system engenders an electron injection route based on collisional quenching between the detached solution-phase dye and dispersed n-type TiO 2 particles, in addition to the general fast electron injection pathway from dye chemisorbed on TiO 2 . For porphyrinsensitized hetero-binary hybrids prepared by mixing a solution-phase Zn porphyrin sensitizer (ZnP) and heterogeneous Re(I) molecular catalystimmobilized TiO 2 particles (TiO 2 /Re(I))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(52 citation statements)
references
References 81 publications
4
48
0
Order By: Relevance
“…In addition, as it has been suggested that Mott–Schottky analysis is not suitable for characterizing bulk TiO 2 nanoparticles with a high concentration of defects, the E fb values of TiO 2 were further estimated using the spectroelectrolysis technique discovered by Grätzel et al, whereby the number of electrons in the CB at a given applied potential can be determined employing visible/near-infrared absorption spectroscopy. The measured E fb values were within a similar range as those commonly obtained using Mott–Schottky analysis, illustrating the significant proton dependence of the E fb level arising from the establishment of a proton adsorption–desorption equilibrium. In practical terms, this spectroelectrolysis technique is the most reliable for determining the E fb of polycrystalline TiO 2 materials, which are commonly used in TiO 2 -based hybrid systems. Figure shows a comparison of the excited-state energies of the organic and organometallic components (photosensitizer and catalyst, respectively) and the band energetics of TiO 2 , which can be varied with different Brønsted acid additives and is determined using the spectroelectrolysis analysis tool.…”
Section: Interfacial Electron Transfer In Miom Systemssupporting
confidence: 68%
See 3 more Smart Citations
“…In addition, as it has been suggested that Mott–Schottky analysis is not suitable for characterizing bulk TiO 2 nanoparticles with a high concentration of defects, the E fb values of TiO 2 were further estimated using the spectroelectrolysis technique discovered by Grätzel et al, whereby the number of electrons in the CB at a given applied potential can be determined employing visible/near-infrared absorption spectroscopy. The measured E fb values were within a similar range as those commonly obtained using Mott–Schottky analysis, illustrating the significant proton dependence of the E fb level arising from the establishment of a proton adsorption–desorption equilibrium. In practical terms, this spectroelectrolysis technique is the most reliable for determining the E fb of polycrystalline TiO 2 materials, which are commonly used in TiO 2 -based hybrid systems. Figure shows a comparison of the excited-state energies of the organic and organometallic components (photosensitizer and catalyst, respectively) and the band energetics of TiO 2 , which can be varied with different Brønsted acid additives and is determined using the spectroelectrolysis analysis tool.…”
Section: Interfacial Electron Transfer In Miom Systemssupporting
confidence: 68%
“…In our recent reports, we have demonstrated that collisional ET from the solvated porphyrin dye to the heterogeneous TiO 2 semiconductor suspended in a reaction solution can serve as a major ET route under conditions wherein the free dye and heterogeneous TiO 2 /catalyst particles coexist in a single reaction vessel (Figure 7). 32 The high activation energies for the collisional electron injection process (57−58 kJ/mol, solvated porphyrin dye → TiO 2 ), which were quantified by means of Arrhenius analysis, indicate that the ET is inefficient because of the low probability of collisions between the solutionphase anionic dye (porphyrin •− ) and heterogeneous TiO 2 particles. 35 However, our photolysis and photodynamic study results demonstrated that the long lifetime of the reductively quenched porphyrin dye (porphyrin •− , τ ∼ minutes), readily obtained in the presence of excess electron donor, can overcome the slow heterointerfacial ET kinetics, effectively increasing the collisional quenching probability of porphyrin •− toward the TiO 2 surface.…”
Section: Types Of Electron Injection (Direct Et Vs Diffusion-mediated...mentioning
confidence: 99%
See 2 more Smart Citations
“…The relatively lower conversion activities of the ternary hybrid can be understood in terms of the lower light-harvesting activity of TiO 2 -bound IrP derived from the considerable light-scattering effects of TiO 2 particles floating in reaction solvent, unlike the homogeneous system. 50,51 The enhanced durability of the ternary hybrid is attributed to the retarded photodegradation of the photosensitizing unit by TiO 2 heterogenization (Figures S11 and S12), as demonstrated by our previous reports. 41,43,46,50,51 This is reminiscent of similar findings in the case of ternary hybrids based on Re(I) catalyst (dye/TiO 2 /Re(I) catalyst).…”
Section: ■ Introductionsupporting
confidence: 70%